Green tea as an effective antimicrobial for urinary tract infections caused by Escherichia coli - Reygaert, Wanda; Jusufi, Ilir (Frontiers in Microbiology, 2013)
Background: Urinary tract infections (UTIs) are a very most common type of infection worldwide, and result in billions of dollars in medical care costs. Escherichia coli is the infective agent for 80–90% of all UTIs. Green tea, derived from leaves of the Camellia sinensis plant has been shown to have various potential health benefits (e.g., cardiovascular disease and cancer). The major beneficial components of green tea have been characterized, and are now known to be polyphenolic catechins. The main catechins in green tea are (-)-epicatechin-3-gallate, (-)-epigallocatechin (EGC), (-)-epicatechin, and (-)-epigallocatechin-3-gallate (EGCG). EGCG and EGC have been shown to have the greatest antimicrobial effects, but only EGC has been shown to be excreted in urine. Isolates of E. coli from UTIs collected between 2007 and 2008 were characterized for antimicrobial resistance to standard drugs. Then 80 of these isolates, representing a wide spectrum of antimicrobial susceptibility patterns, were selected for testing using an extract of green tea. Results: The concentrations of green tea extract tested were 0, 2.5, 3.0, 3.5, and 4.0 mg/ml. All of the strains tested, except one, had minimum inhibitory concentrations (MICs) of ≤4.0 mg/ml (99%), with 94% of the isolates having an MIC of ≤3.5 mg/ml, 76% of the isolates having an MIC of ≤3.0 mg/ml, 40% of the isolates having an MIC of ≤2.5 mg/ml. Two control strains varied in susceptibility, one having an MIC of ≤2.5 mg/ml,and the other having an MIC of ≤3.5 mg/ml. Conclusion: Since EGC has been shown to have antimicrobial effects on E. coli, and EGC has been shown to be excreted in the urine in a high enough concentration to potentially be effective as an antimicrobial; these MIC results suggest that ingesting green tea could have potential antimicrobial effects on UTIs caused by E. coli.